PERAN STAKEHOLDER DALAM PENGEMBANGAN DESA WISATA DI DESA WISATA KAMASAN, KABUPATEN KLUNGKUNG - Purnama Sari, Made Ayu; Wijaya, Komang Adi Sastra; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2024)
Kamasan Tourism Village is one of 19 tourist villages in Klungkung Regency which is still facing obstacles in its development. This study aims to analyze the role of stakeholders in the development of tourism villages in Kamasan Tourism Village. This research uses descriptive qualitative methods. Data collection was carried out by observation, interview, documentation methods. Analysis of the findings uses Governance theory according to Sedarmayanthi (2012) through the three pillars of Stakeholders namely: government, private sector, and society. The findings show that the government's role is not optimal, the role of the private sector is also not maximized. The role of the community is quite good. The recommendation that the author can give is that the government must record existing craftsmen, and the private sector must implement existing craft product innovations. Keywords: Stakeholder Role, Development, Tourism Village